Perceived Job Attributes and Intention to Join Among MBA Students - Dubey, Shalini; Misra, Rajnish Kumar (Prabandhan: Indian Journal of Management, 2024)
Today, with globalization, when companies are trying too hard to â€œattract and retain the best talent,â€ the new graduates are searching for preferred attributes in a job/organization. Consequently, when the companies advertise the vacancies, the students prefer to join the company that is closer to what they regard as the â€œideal employer.â€ The present paper proposed to understand the impression of perceived job attributes concerning employer branding perspective from the MBA final year students and discussed its significance in influencing the studentâ€™s decisionmaking process. Our study explored the existing literature for perceived job attributes and analyzed them using descriptive research analysis. A theoretical framework was proposed and tested with 411 valid data points. Structural equation modeling (SEM) was used to test the proposed framework. The empirical study revealed that the â€œperceived job attributesâ€ positively influenced the â€œintention to joinâ€ the company. The implications suggest that MBA graduates are significant assets to a business and have a substantial role in the future growth of the company, therefore, it was important to understand their perspective on choosing the right company associated with numerous benefits.